2018
DOI: 10.1177/0097700418811072
|View full text |Cite
|
Sign up to set email alerts
|

Political Resources and Divergent Court Empowerment in China: A Subnational Comparison

Abstract: The cities of Guiyang and Kunming are known among legal scholars, practitioners, and policy makers for hosting two of China’s earliest specialized environmental tribunals, following serious water contamination in the two cities. However, the judicialization of environmental protection appears to be relatively nominal in Kunming and substantial in Guiyang. Why? We contend that, at a critical juncture, different political resources available to local leaders—including their past networks and experiences—led them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…This summary indicates a resource‐centric pattern of judicial expansion. Based on a comparison of environmental adjudication in Guiyang and Kunming, Wang and Liang concluded that the individual party‐state leader's political resources—such as their past networks and experiences—determine whether judicialization in their jurisdiction is nominal or substantial (Wang & Liang, 2019). Taking the argument a step further, this study suggests that a key determining factor for judicial empowerment is the resources available to various types of legal actors, such as NGOs, procuratorates, and courts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This summary indicates a resource‐centric pattern of judicial expansion. Based on a comparison of environmental adjudication in Guiyang and Kunming, Wang and Liang concluded that the individual party‐state leader's political resources—such as their past networks and experiences—determine whether judicialization in their jurisdiction is nominal or substantial (Wang & Liang, 2019). Taking the argument a step further, this study suggests that a key determining factor for judicial empowerment is the resources available to various types of legal actors, such as NGOs, procuratorates, and courts.…”
Section: Discussionmentioning
confidence: 99%
“…Such differences can be largely attributed to China's relatively closed national political system, under which no decisions made at the highest levels can be challenged in court-neither de jure nor de facto. Nevertheless, China's more localized pattern of judicialization fits the generally accepted definition of the term-the "delegation of power to courts by political and administrative actors" (Hirschl, 2007;Wang & Liang, 2019). Furthermore, it is arguably no less significant than the judicialization of higher politics in many other authoritarian countries, a fact highlighted by China's relative success at boosting its "rule of law" ratings in the past decade (Wang, 2020c).…”
Section: Judicial Expansion Under Democracy and Authoritarianismmentioning
confidence: 97%
See 1 more Smart Citation
“…The agenda and outreach activities of a court generally follow the local government's broader policy agenda. For instance, when a local government emphasizes innovation and prioritizes environmental protection, the local court may propose a pioneering environmental tribunal and collaborate with the Bureau of Environmental Protection (Wang & Liang, 2019).…”
Section: Institutional Proximity For Chinese Courtsmentioning
confidence: 99%
“…As part of legal reform the government directs decision-making by mostly local officials to courts, not allowing party officials to intervene in judicial processes (Liebman, 2017). Wang and Liang (2019) demonstrate that government officials also empower courts to effectively respond to environmental protection in Guiyang. The Chinese political system is therefore not characterized by a fully centralized hierarchical structure; instead, China experts have long emphasized the fragmented nature of the Chinese authoritarian state promoting legal reforms for more effective governance (see, for example, Lieberthal and Lampton, 1992).…”
Section: China's Legal System and The Approach Towards Content Managementioning
confidence: 99%